2010
DOI: 10.1609/icwsm.v4i1.14031
|View full text |Cite
|
Sign up to set email alerts
|

From Tweets to Polls: Linking Text Sentiment to Public Opinion Time Series

Abstract: We connect measures of public opinion measured from polls with sentiment measured from text. We analyze several surveys on consumer confidence and political opinion over the 2008 to 2009 period, and find they correlate to sentiment word frequencies in contempora- neous Twitter messages. While our results vary across datasets, in several cases the correlations are as high as 80%, and capture important large-scale trends. The re- sults highlight the potential of text streams as a substi- tute and suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 962 publications
(126 citation statements)
references
References 16 publications
0
124
0
2
Order By: Relevance
“…In fact, researchers have recently begun to use the content of Twitter messages to measure and predict real-world phenomena, including movie box office returns (Asur and Huberman 2010), elections (O'Connor et al 2010), and the stock market (Bollen, Mao, and Zeng 2010). While these studies show remarkable promise, one heretofore unanswered question is: Are Twitter users a representative sample of society?…”
Section: Introductionmentioning
confidence: 99%
“…In fact, researchers have recently begun to use the content of Twitter messages to measure and predict real-world phenomena, including movie box office returns (Asur and Huberman 2010), elections (O'Connor et al 2010), and the stock market (Bollen, Mao, and Zeng 2010). While these studies show remarkable promise, one heretofore unanswered question is: Are Twitter users a representative sample of society?…”
Section: Introductionmentioning
confidence: 99%
“…Pak and Patrick divided the individual tweets into positive, negative, or neutral categories that could better understand sentiments by the computer (Pak and Paroubek, 2010). O'Connor et al indicated that the sentiments in tweets reflect the public opinion on various topics in public opinion surveys (O'Connor et al, 2010). This study identified sentiment analysis as a more cost-effective option versus public opinion surveys.…”
Section: Introductionmentioning
confidence: 78%
“…Several machine learning methods, supervised and unsupervised, have been developed to predict such events. The linear regression models use simple features to predict the occurrence time of future events (O'Connor et al, 2010;Bollen et al, 2011;He et al, 2013;Arias et al, 2014). More advanced techniques use features such as topic-related keywords as input to support vector machines, LASSO, and multi-task learning approaches (Ritterman et al, 2009;Wang et al, 2012).…”
Section: Forecasting Civil Unrest and Geopolitical Eventsmentioning
confidence: 99%